2022
DOI: 10.3390/vaccines10060884
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Subset Redistribution and Antibody Dependent Activation after Ebola Vaccination in Africans

Abstract: Natural killer cells play an important role in the control of viral infections both by regulating acquired immune responses and as potent innate or antibody-mediated cytotoxic effector cells. NK cells have been implicated in control of Ebola virus infections and our previous studies in European trial participants have demonstrated durable activation, proliferation and antibody-dependent NK cell activation after heterologous two-dose Ebola vaccination with adenovirus type 26.ZEBOV followed by modified vaccinia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…In vitro stimulation/inhibition studies using EBOV GP indicated that NK cell activation was dependent on IL-18 and IL-12 and could be enhanced by an antagonist that blocked the IL-10 receptor 107 . Two NK cell activation markers, CD107a and CD25, were observed to be upregulated in response to EBOV GP but without secretion of type II IFNγ usually synthesised by both NK and T cells 108 . Simultaneously the EBOV VP40 protein subunit domain was found to stimulate IL-12/IL-18 production 109 .…”
Section: Natural Killer Cells During Immune Responses To Ebola Virusmentioning
confidence: 95%
“…In vitro stimulation/inhibition studies using EBOV GP indicated that NK cell activation was dependent on IL-18 and IL-12 and could be enhanced by an antagonist that blocked the IL-10 receptor 107 . Two NK cell activation markers, CD107a and CD25, were observed to be upregulated in response to EBOV GP but without secretion of type II IFNγ usually synthesised by both NK and T cells 108 . Simultaneously the EBOV VP40 protein subunit domain was found to stimulate IL-12/IL-18 production 109 .…”
Section: Natural Killer Cells During Immune Responses To Ebola Virusmentioning
confidence: 95%
“…In vitro stimulation/inhibition studies using EBOV GP indicated that NK cell activation was dependant on IL-18 and IL-12 and could be enhanced by an antagonist that blocked the IL-10 receptor 107 . Two NK cell activation markers, CD107a and CD25, were observed to be upregulated in response to EBOV GP but without secretion of type II IFNγ usually synthesised by both NK and T cells 108 . Simultaneously the EBOV VP40 protein sub-unit domain was found to stimulate IL-12/IL-18 production 109 .…”
Section: Natural Killer Cells During Immune Responses To Ebola Virusmentioning
confidence: 95%